Peaches at Medieval Site Ras, Serbia: Unraveling Routes of Introduction and Local Cultivation in the Balkans - Borojević, Ksenija; Jagusiak, Krzysztof; Gašić, Ksenija (Studia Ceranea, 2024)
The study combines archaeological evidence, written sources, and genetic studies to trace the routes of peach introduction to the Balkans and explore the local cultivation practices and it revisits the discovery of peach remains at the medieval site of Ras in southwest Serbia. Peach (Prunus persica [L.] Batsch) came to the Mediterranean from the East around the 6th/4th c. BC, and over the following centuries it spread westwards. In the Roman Empire it was an already well known fruit. One possible route for its introduction to Europe was through the Balkans (“via Balcani”), from the Black Sea region along the Danube River to other areas. However, following the Migration Period and the fall of the Western Roman Empire, the peach tree orchards remained mostly abandoned for the next three centuries. In contrast, the peach trees in the Eastern (Byzantine) Empire remained present despite repeated invasions, and destructive conflicts, which occurred between the 5th–11th/12th centuries. Peaches were generally available on the market and described in written sources. Archaeological evidence of the of peaches in the region can be found at the medieval site Ras in Serbia, where peach fruit stone fragments have been radiocarbon dated to 1021–1158 cal AD. During the 12th century, Ras served as a Byzantine fortress and later became the main defensive stronghold of the newly formed Serbian state from the middle of the 12th century to the fourth decade of the 13th century. Given the peach fruit soft texture and difficulty to transport, it is likely that they were grown locally. The Romans could have introduced peaches into the area during the 4th century. However, the area was abandoned between the 6th–9th centuries and the peach trees could not have survived if unattended. In the Balkans, including present-day Serbia, there is a significant genetic diversity of peach landraces that are grown effectively wild in vineyards (“vineyard peach”) and are ancient in origins. The presence of peach stones at Ras suggests a possible continuity of practices linked to the “via Balcani” route and enduring local cultivation or trade from southern regions since ancient times. Future discoveries of peach stones in the area will enhance our understanding of this historical route. This study provides significant insights into the prolonged existence and local cultivation of peaches in the broader region, emphasizing the interplay between cultural exchange, trade, and agricultural practices over millennia.